2014
DOI: 10.3844/ajavsp.2014.252.262
|View full text |Cite
|
Sign up to set email alerts
|

Evidences for the Role of Melatonin as a Protective Additive During Buffalo Semen Freezing

Abstract: Till now, the exact role of melatonin in male infertility hasn't been fully discovered. Moreover, the intracellular signaling pathways activated by melatonin in buffalo spermatozoa especially on the level of cryopreservation process haven't been reported. The current study aimed simply to clarify the precise role of this hormone during buffalo semen cryopreservation. Semen samples were obtained randomly from 6 fertile buffalo bulls (aged 3 to 5 years). Weekly, two consecutive ejaculates were collected from eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 69 publications
5
20
2
1
Order By: Relevance
“…Additionally, the percentages of post-thaw primary and secondary sperm abnormalities were 2.6 and 3.6 higher in the control group than those of MelatoninHD group, respectively. These results are in conformity with those reported previously in different species (Sariözkan et al 2009;El-Raey et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Additionally, the percentages of post-thaw primary and secondary sperm abnormalities were 2.6 and 3.6 higher in the control group than those of MelatoninHD group, respectively. These results are in conformity with those reported previously in different species (Sariözkan et al 2009;El-Raey et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, via modulating the glutathione activity, melatonin has been reported to improve sperm mitochondrial health state and functions and, thus, improve IVF outcomes (El-Raey et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Gualtieri et al (2014) revealed that adding 10 µg mL −1 zinc chloride, 500 µg mL −1 D-aspartate and 40 µg mL −1 coenzyme Q10 to the bull semen after thawing improved all kinetic motilities of semen as compared to the control group. El-Raey et al (2014) found that addition of 1 mM of melatonin for tris-based egg yolk diluent improved sperm motility, viability values and the fertility rate as well compared to control group in buffalo bulls. Moreover, Daramola and Adekunle (2015) found that the progressive motility of chilled buck semen were improved in extender that was supplemented with pineapple and cucumber juices compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…Where, melatonin was found to directly interact with ROS and stimulates the activity of some antioxidant enzymes as superoxide dismutase, glutathione peroxidase, and catalase [16,17]. Also, melatonin prevents lipid peroxidation [39]; protein, and DNA [19,40]. In addition, it was found that melatonin preserve the function of mitochondria through reducing and preventing ROS [20], as well as enhancing mitochondrial distribution activity and patterns during nuclear maturation phase [31], and preventing or reducing apoptosis level [21].…”
Section: Discussionmentioning
confidence: 99%